IL-10 in Antilipopolysaccharide Immunity Against Systemic Klebsiella Infections - Tomislav Rukavina; Brigita Ticac; Vanja Vasiljev (Mediators of Inflammation)
Aim. This study was undertaken in order to determine whether anti-inflammatory cytokine interleukin-10 is responsible for a previously described protection against Klebsiella infection mediated by antilipopolysaccharide antibodies. Methods. BALB/c mice were infected intraperitoneally with a lethal challenge of Klebsiella pneumoniae Caroli. One group was protected with monoclonal antibodies prior to infection and the second was not. We measured plasma levels of interleukin-10 at different time points by enzyme immunoassay and analyzed the relation between interleukin-10 and proinflammatory cytokines interleukin-6 and tumor necrosis factor-α in order to determine the association of these ratios with the outcome of infection. Major findings and conclusions. We found different pattern of interleukin-10 production in protected mice compared with unprotected ones. The difference is greatest 24 hours postinfection. The ratios between IL-10 and proinflammatory cytokines confirmed the suppressed proinflammatory response in protected animals, especially 24 hours postinfection. Hence the mortality in unprotected mice begins immediately after we conclude that such cytokine relation and IL-10 production are, at least partially, responsible for the destiny of infected animals and the outcome of infection.